Professor D.M. Davies, founder of Adverse Drug Reaction Bulletin: a tribute on the 50th anniversary of Adverse Drug Reaction Bulletin. (December 2016) - Routledge, Philip A.
Abstract : Summary: The Adverse Drug Reaction Bulletin has been published bimonthly for the last 50 years. The format has remained the same with four sides of approximately 2000 words on an important adverse reaction, but has grown from sheets stencilled for distribution locally to a bulletin with a large circulation both in English and Italian. Its aim remains, as then, to provide a succinct summary of the causes and mechanisms of a particular adverse reaction, or the types of reactions which affect a particular system organ class.